EFL STUDENTS’ PERCEPTIONS OF GRAMMARLY FOR GRAMMAR ACCURACY AND INDEPENDENT LEARNING IN THE ERA OF EDUCATION 5.0 - Lili Sururi Asipi; Aldha Williyan; Angga Adi Saputra (University of Kuningan, 2026)
The integration of artificial intelligence (AI) into English as a Foreign Language (EFL) instruction has reshaped feedback practices in academic writing, particularly through Automated Writing Evaluation (AWE) tools such as Grammarly. Within the Education 5.0 paradigm, AI is expected to support human-centered learning, reflective engagement, and learner autonomy rather than replace teacher mediation. This study explores Indonesian EFL students’ perceptions of Grammarly in supporting grammatical accuracy, independent learning, and writing confidence. Employing a qualitative-dominant research design, data were collected from 100 undergraduate EFL students through a descriptive questionnaire and follow-up semi-structured interviews with three purposively selected participants. Quantitative data were analyzed descriptively, while qualitative data were examined using reflexive thematic analysis. The findings indicate that students generally perceived Grammarly as easy to use and helpful in identifying grammatical errors, expanding vocabulary, and improving sentence-level accuracy. Grammarly was also perceived to encourage self-checking and reflective revision; however, learner independence was found to be conditional, as many students still relied on teacher guidance for contextual and rhetorical aspects of writing. In addition, positive affective outcomes emerged, including increased confidence and reduced anxiety toward writing tasks. Overall, the study suggests that Grammarly functions as a micro-level linguistic scaffold rather than a comprehensive writing tutor. Its pedagogical value is maximized when integrated within teacher-guided instructional frameworks that promote critical engagement with AI feedback, aligning with the human-centered principles of Education 5.0.